18-Fluorodeoxyglucose positron emission tomography/computed tomography for large vessel vasculitis in clinical practice - Nassarmadji, Kladoum; Vanjak, Anthony; Bourdin, Venceslas; Champion, Karine; Burlacu, Ruxandra; Mouly, Stéphane; Sène, Damien; Comarmond, Cloé (Frontiers in Medicine, 2023)
Diagnosis, prognostic assessment, and monitoring disease activity in patients with large vessel vasculitis (LVV) can be challenging. Early recognition of LVV and treatment adaptation is essential because vascular complications (aneurysm, dilatations, ischemic complications) or treatment related side effects can occur frequently in these patients. 18 FDG-PET/CT is increasingly used to diagnose, follow, and evaluate treatment response in LVV. In this review, we aimed to summarize the current evidence on the value of 18 FDG-PET/CT for diagnosis, follow, and treatment monitoring in LVV.